PRAKTIK PENERAPAN SAP, AKUNTABILITAS DAN TRANSPARANSI DALAM PENGELOLAAN DANA DESA - Oktavia, Yohana (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to determine the effect of the application of government accounting standards, accountability and transparency on the management of the Village Fund. The location is located in villages in the Ngancar District, Kediri Regency. This type of research uses quantitative. Population 135. Using side purposive with a total of 60 respondents. The data analysis technique uses the classical assumption test, multiple linear regression analysis at a significance level of 5%, the termination coefficient test, t and f tests using the SPSS 25 application. With the results that the application of SAP has a significant effect on the management of village funds, accountability has a significant effect on the management of funds Village funds and transparency have no significant effect on the management of village funds and simultaneously the application of SAP, accountability and transparency has a significant effect on the management of village funds.